Landslide Susceptibility Analysis of Geological Formations: A Case Study of the Dupi Tila Formation in the Rangamati Area - Hossain, Shakhawat; Tushar, Mahmud Al Noor; Islam, Shariful; Razzak, Md Zayed Abdur; Hossain, Sushmita; Rajib, Mohammad (The Dhaka University Journal of Earth and Environmental Sciences, 2023)
This study investigates the landslide susceptibility of the Dupi Tila Formation by analyzing geological parameters such as lithology, clay mineralogy, rock weathering, and structural features. The Dupi Tila Formation comprises poorly consolidated sandstone and shale layers. The percentage of mudrocks in this formation is about 32- 38%. X-ray diffraction (XRD) analysis identified illite, chlorite, smectite, and kaolinite as the major clay minerals present in the formation. The qualitative analysis of the degree of weathering in outcrops shows a high degree of weathering indicated by the disintegration of grains and the presence of chemically altered minerals. Chemical Index of Alteration (CIA), Modified Potential Weathering Index (MPWI), and Kornberg Weathering Index (A) computed from the major oxide concentration of Dupi Tila Formation suggest that the weathering potential of this formation is high. The formation contains closely spaced bedding planes and two crisscrossing joints that can act as planes of weakness. Landslides can be triggered by the repeated widening of these planes of weakness caused by the saturation of clay minerals during periods of heavy rainfall. The comparable sizes of the fallen rock blocks and the joint spacings imply that structural features have played a role in landslide occurrences. Rockfall, topple, and translational slides are the major landslide types in the formation. While the position of the formation in the flank of the anticline makes the slope unfavorable for landslide occurrences, intense rainfall, and slope modification can make it susceptible to landslides. The results of this study demonstrate the significant impact of geological factors on landslide occurrences. Thus, a detailed geological analysis should be integrated into the landslide susceptibility analysis workflow to accurately identify and delineate at-risk areas. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 11(2), 2022, P 1-13